1992
DOI: 10.1017/s0890037x00034722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil-Applied AC 263,222 on Crops Rotated with Soybean (Glycine Max)

Abstract: The effects of the imidazolinone herbicide AC 263,222 on crops that may be rotated with soybean were studied in the greenhouse and field. Corn, grain sorghum, cotton, rice, wheat, soybean, and Italian ryegrass were planted directly into treated soil after AC 263,222 was incorporated. In the field, AC 263,222 at rates as high as 35 g ai ha–1did not reduce shoot weight or emergence of these species. Some visual injury occurred, but was 20% or less 28 d after planting for all crops. Crops were more sensitive in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
15
0
4
Order By: Relevance
“…Ulbrich et al (1998) worked with soils in the Londrina region and reported corn PINYDs after soybean of 87 d for imazapyr and 112 d for imazaquin. Wixson and Shaw (1992) reported greater tolerance of corn to imazapic (35 g ai/ha) than to imazaquin (6 g ai/ha) when the herbicides were incorporated into the soil and the crop planted immediately. Bovey and Senseman (1998) found that corn was less tolerant to imazapyr residues compared with soybean or edible beans.…”
Section: Resultsmentioning
confidence: 99%
“…Ulbrich et al (1998) worked with soils in the Londrina region and reported corn PINYDs after soybean of 87 d for imazapyr and 112 d for imazaquin. Wixson and Shaw (1992) reported greater tolerance of corn to imazapic (35 g ai/ha) than to imazaquin (6 g ai/ha) when the herbicides were incorporated into the soil and the crop planted immediately. Bovey and Senseman (1998) found that corn was less tolerant to imazapyr residues compared with soybean or edible beans.…”
Section: Resultsmentioning
confidence: 99%
“…Cabe destacar que o efeito residual dos herbicidas do grupo das imidazolinonas pode apresentar diferentes prejuízos a culturas não tolerantes, variando conforme o manejo da área, o clima, a umidade do solo, a quantidade de herbicida aplicado, entre outros fatores que contribuem para a sua persistência no solo. Os danos registrados para o efeito do residual desses herbicidas vão desde redução no estande da planta e da massa seca (Renner et al, 1988;Zhang et al, 2002;Matocha et al, 2003;Villa et al, 2006a), do tamanho das raízes (Wixson & Shaw, 1992), até redução da produtividade, como demonstrado por esta pesquisa e por outros autores (Loux & Reese, 1993;Zhang et al, 2002).…”
Section: Resultsunclassified
“…Esses dados demonstraram que as doses de imazapic utilizadas foram adequadas para as plantas de cana-de-açúcar, pois, segundo a pesquisa de Wixson & Shaw (1992), o uso de imazapic a 35 g ha -1 nas culturas de algodão e milho proporcionou sintomas de intoxicação mais elevados aos 28 DAT.…”
Section: Resultsunclassified
“…Wixson & Shaw (1991b) ) em pós-emergência inicial, proporcionou injúrias de até 13%, aos 56 DAT. Segundo Wixson & Shaw (1992), a aplicação em pré-plantio de imazapic (9, 18 e 35 g ha -1 ) também causou até 20% de injúria inicial em diferentes culturas. Além das doses e do modo de aplicação, Wixson & Shaw (1991a) demonstraram que a adição de surfatante ou óleo concentrado colabora para o aumento da toxicidade na soja.…”
Section: Introductionunclassified